Highly efficient removal of As(III), Zn(II), Cu(II) and Cd(II) in aqueous solution using thermal desorption residue from oil sludge contaminated soil: Performance and mechanism. Issue 3 (June 2022) - Zhang, Ge; Yang, Huifen; Zhao, Tong; Li, Xuan; Zhou, Yichen; Guo, Song
Abstract: The thermal adsorption residue (TDR) from oil sludge co-contaminated soil was employed to remove As(III), Zn(II), Cu(II), Cd(II) in aqueous solution. The results showed that the TDR could efficiently neutralize the acid and adapt to the extensive pH. The adsorption of four heavy metals on TDR could be divided into three stages. The maximum adsorption capacity were 86.59, 249.07, 339.88, 322.86 mg·g −1 for As(III), Zn(II), Cu(II), Cd(II), respectively. The coexistence of Zn(II)/Cu(II)/Cd(II) could promote As(III) removal but As(III) led to decreasing of Zn(II)/Cu(II)/Cd(II) adsorption capacity in binary system. There was a significant competitive adsorption on TDR among the three cations which followed the selectivity sequence of Cu(II)>Zn(II)>Cd(II). The SEM-EDS, XRD, FTIR and XPS analyses demonstrated that the As(III) was removed via formation of Ca-As precipitation, and the Zn(II), Cu(II), Cd(II) were removed through precipitating as hydroxides/carbonates/silicates combining with ion exchange. Specially, the Cu(II) mainly precipitated in the form of Cu4 (SO4 )(OH)6 ⋅2H2 O and Cu4 (OH)6 SO4 under sulfuric acid solution environment. Overall, this study indicates the potential of TDR as a cost-effective adsorbent in acid heavy metals contaminated wastewater treatment. Graphical Abstract: ga1 Highlights: TDR showed excellent adsorption capacity for As(III), Zn(II), Cu(II) and Cd(II). High interference among the HMs was observed in binary adsorption system. As(III) was removed via the formation of Ca-As precipitation. Zn(II)/Cu(II)/Cd(II) were removed through chemical precipitating and ion exchange. SO4 2− promoted the precipitation of Cu(II) as Cu4 (SO4 )(OH)6 ⋅2H2 O and Cu4 (OH)6 SO4 .